The Dialectics of “Master-Slave” and the Longing for Overcoming Solipsism - Baranova, Jūratė (Problemos, 2003)
This article asks on what theorethical grounds the relation between Me and the Other is based in Sartrean existential phenomenology. Why Sartre is dissatisfied with the notion of transcendental ego delivered by Immanuel Kant? Why Sartre, starting from Husserl, does not accept the relation between Me and the Other as alter ego explicated in the fifth Cartesian Meditation? Why he turns toward the dialectics of "master-slave" found in the Phenomenology of Spirit by Georg Hegel? Why this dialectics is incompatible with the modus of Mitsein in Martin Heidegger fundamental ontology? Sartre seeks to reveal the possibility of meeting the Other in the battle of freedoms by the analysis of concrete relations with the Other and by this to avoid solipsism. But do I really meet the Other if each confrontation between two freedom inescapably ends with the defeat?
Keywords: Kant; Sartre; solipsism; dialectics of "master-slave"; concrete relations with Other